Racioethnic disparities in comorbidities and outcomes following head and neck oncologic surgery - Usama Waqar; Aahan Arif; Ayesha N. Hameed; Syeda M. A. Zaidi; Muhammad Hamza; Haissan Iftikhar; Huma Naz; Syed A. Abbas (World Journal of Otorhinolaryngology-Head and Neck Surgery)
Abstract Objectives Racial disparities persist despite attempts to establish an egalitarian framework for surgical care. This study aimed to investigate racioethnic disparities in comorbidities and outcomes following surgery for head and neck tumors. Methods This retrospective study included adult patients who underwent head and neck oncologic surgery between 2008 and 2020 from the National Surgical Quality Improvement Program. Multivariable regression analyses were conducted to explore the association of the following racioethnic categories with postoperative outcomes: White, Black, Hispanic, and Asian. Results A total of 113,234 patients were included in the study, comprising 78.3% White, 8.7% Black, 6.9% Hispanic, and 6.0% Asian patients. Black patients had higher rates of pre‐existing comorbidities compared to White patients. Specifically, the rates of comorbidities such as diabetes mellitus (19.8% vs. 12.4%), hypertension (57.5% vs. 41.5%), smoking history (18.8% vs. 15.0%), dyspnea (7.4% vs. 5.7%), and preoperative anemia (43.6% vs. 36.5%) were higher among Black patients. On regression analyses, Black race was not associated with major morbidity following head and neck oncologic surgeries (odds ratio, 1.098, 95% confidence interval, 0.935–1.289) when compared to White patients. However, there were significant associations between the comorbidities associated with the Black race and an increased risk of major morbidity. Conclusions Black patients undergoing head and neck oncologic surgery face a significant challenge due to a higher burden of comorbidities. These comorbidities, in turn, have been found to be associated with postoperative major morbidity.